2017
DOI: 10.1111/cas.13127
|View full text |Cite
|
Sign up to set email alerts
|

Combined fibrinogen and neutrophil‐lymphocyte ratio as a prognostic marker of advanced esophageal squamous cell carcinoma

Abstract: Patients with advanced esophageal squamous cell carcinoma (ESCC) is received chemoradiotherapy or chemotherapy for clinical management. However, it is difficult to predict tumor response and prognosis using blood markers before starting treatments. The purpose of this study was to investigate the pre‐treatment plasma fibrinogen and neutrophil–lymphocyte ratio (NLR) in patients with advanced ESCC treated with chemoradiotherapy or chemotherapy, and to assess the clinical utility of a combined score using these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 38 publications
6
67
0
Order By: Relevance
“…Furthermore, higher F-NLR scores were associated with larger tumor size, deeper tumor invasion, and lymph node metastasis. This observation was in line with previous studies that indicated that the F-NLR score was significantly correlated with tumor progression and aggressive biological behavior 14,15. In subgroup analyses, the F-NLR score still exhibited potential prognostic value, as shown in Figures 2 and 3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, higher F-NLR scores were associated with larger tumor size, deeper tumor invasion, and lymph node metastasis. This observation was in line with previous studies that indicated that the F-NLR score was significantly correlated with tumor progression and aggressive biological behavior 14,15. In subgroup analyses, the F-NLR score still exhibited potential prognostic value, as shown in Figures 2 and 3.…”
Section: Discussionsupporting
confidence: 91%
“…Many investigators have demonstrated the clinical utility of fibrinogen as a prognostic predictor in various types of malignancies 12,13. Recently, a new scoring system combining preoperative fibrinogen and the NLR (F-NLR) has been demonstrated as a promising prognostic marker for esophageal squamous cell carcinoma 14,15. However, the prognostic role of F-NLR in GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have emphasized that hyperfibrinogenemia is involved in the malignant behaviors of various types of cancer (Kijima et al, ; Lu et al, ; Qiu et al, ). And the elevated preoperative plasma fibrinogen levels are associated with worse outcome in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…17 Based on NLR values, an additional prognostic score, combining NLR and fibrinogen levels (F-NLR), has been proposed in different tumors, 18 with interesting results. 19 The aim of our study was to investigate the correlation between NLR, fibrinogen, and F-NLR with survival in our OC population.…”
mentioning
confidence: 99%